Egg consumption and cardiovascular disease according to diabetic status: The PREDIMED study. Issue 4 (August 2017) - Díez-Espino, J.; Basterra-Gortari, F.J.; Salas-Salvadó, J.; Buil-Cosiales, P.; Corella, D.; Schröder, H.; Estruch, R.; Ros, E.; Gómez-Gracia, E.; Arós, F.; Fiol, M.; Lapetra, J.; et al.
Summary: Background: Eggs are a major source of dietary cholesterol and their consumption has been sometimes discouraged. A relationship between egg consumption and the incidence of cardiovascular disease (CVD) has been suggested to be present exclusively among patients with type2 diabetes. Aims: To assess the association between egg consumption and CVD in a large Mediterranean cohort where approximately 50% of participants had type 2 diabetes. Methods: We prospectively followed 7216 participants (55–80 years old) at high cardiovascular risk from the PREDIMED (PREvención con DIeta MEDiterránea) study for a mean of 5.8 years. All participants were initially free of CVD. Yearly repeated measurements of dietary information with a validated 137-item food-frequency questionnaire were used to assess egg consumption and other dietary exposures. The endpoint was the rate of major cardiovascular events (myocardial infarction, stroke or death from cardiovascular causes). Results: A major cardiovascular event occurred in 342 participants. Baseline egg consumption was not significantly associated with cardiovascular events in the total population. Non-diabetic participants who ate on average >4 eggs/week had a hazard ratio (HR) of 0.96 (95% confidence interval, 0.33–2.76) in the fully adjusted multivariable model when compared with non-diabetic participants who reported the lowest egg consumption (<2 eggs/week). Among diabetic participants, the HR was 1.33 (0.72–2.46). There was no evidence of interaction by diabetic status. HRs per 500 eggs of cumulative consumption during follow-up were 0.94 (0.66–1.33) in non-diabetics and 1.18 (0.90–1.55) in diabetics. Conclusions: Low to moderated egg consumption was not associated with an increased CVD risk in diabetic or non-diabetic individuals at high cardiovascular risk. This trial was registered atcontrolled-trials.com as ISRCTN35739639.